Marriage Dispute Resolution in Muslim Populated Countries: A Comparative Study of Divorce Law in Indonesia and Singapore - Mohammad Ainul Hakim Hakim (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose – The issue of reasons for divorce is an interesting discussion to study. In Indonesia, the reason for divorce that is mostly submitted by parties who want to divorce is the dispute between husband and wife. The reason for divorce in Law No. 1 of 1974 is Article 39 paragraph (2), and husband and wife disputes are included as reasons for divorce in the law. Meanwhile, in Singapore, the factors contributing to divorce between husband and wife are also mostly due to husband and wife disputes. The grounds for divorce in Singapore are regulated in Article 49 AMLA 1966 concerning fasakh. Methods – Data collection methods using library research and descriptive-comparative data analysis. The data that has been collected is analyzed using Descriptive Comparative Law Theory. Findings – The results of the research obtained that the provisions of the reasons for divorce under these two laws have differences and similarities. The difference is that Law No. 1 Year 1974 explicitly determines that the dispute between husband and wife is the reason for divorce, while Article 49 AMLA indicates that the provisions therein are factors in the occurrence of husband and wife disputes that are the cause of divorce. The similarity between these two laws is that they require husband and wife to participate in mediation or counseling when one of them files for divorce before proceeding to trial. Research implications/limitations – Based on the conclusions reached, this research recommends the reconstruction of divorce law in Muslim countries. A multidisciplinary approach is expected to maximize the chances of the success of mediation in divorce cases.